Influence of external magnetic wire on natural convection of non-Newtonian fluid in a square cavity - T. Sarala Devi; C. Venkata Lakshmi; K. Venkatadri; M. Suryanarayana Reddy (Partial Differential Equations in Applied Mathematics, 2021)
The augment of heat transfer and intensity of fluid has wide range of application in science and engineering. The buoyancy-driven flow of Casson viscoelastic fluid in a square cavity in the presence of external magnetic field is examined numerically. Cold temperature is applied on the right side (vertical) wall and high temperature is imposed on left wall while the horizontal walls are kept at thermally insulated. The mathematical model comprises mass and primary and secondary momentum conservation equations and boundary conditions imposed at the four sides of the enclosure. The model is non-dimensional and converted into pressure–velocity form. The Harlow–Welch marker and cell (MAC) finite difference technique is employed to solve the nonlinear boundary value problem via pressure–velocity coupling. The developed MATLAB code is validated with previous literature and it gives good agreement. The effects of Rayleigh number Ra, Casson viscoplastic fluid parameter and Hartmann number Ha on the flow and heat transfer characteristics are analyzed. Results indicate that the temperature gradient is an increasing function of the buoyancy force. The heat transfer characteristics and flow behavior are presented in the form of streamlines and isotherms.